Discordance Between Population Impact of Musculoskeletal Disorders and Scientific Representation: A Bibliometric Study. Issue 1 (27th December 2018) - Perruccio, Anthony V.; Yip, Calvin; Power, J. Denise; Canizares, Mayilee; Badley, Elizabeth M.
Abstract : Objective: Musculoskeletal disorders (MSDs) are a leading cause of healthy years lost due to premature mortality and disability. Our objective was to investigate whether MSDs were commensurably represented within the published health literature. Methods: MEDLINE bibliometric data were retrieved for 2011 and 2016. The 25 disease branches, including MSDs, were ranked according to published article counts, proportion of all publications, and increase in publications from 2011 to 2016. Rankings were also considered within 5 groupings of general health journals: geriatrics and gerontology, general and internal medicine, multidisciplinary sciences, primary health care, and public health. Results: There were 532, 283 MEDLINE publications in 2016, a 16% increase over 2011. In 2016, MSDs ranked 13th in publication count, unchanged from 2011. The increase of 11% in MSD publications from 2011 was below the overall increase. Of 2016 publications, only 7% were MSD indexed, dropping from 7.3% in 2011. MSD‐indexed publications had their highest ranking (8th) within geriatrics and gerontology, and lowest (19th) within public health. Conclusion: MSDs appear underrepresented in the published health literature generally, and specifically within public health, despite their significant population impact. A broader focus on noncommunicable diseases associated with mortality omits noncommunicable diseases such as MSDs that are leading contributors to high morbidity and high costs, and such omission likely contributes to the neglect of recognizing MSDs as a health priority.